Concentration fluctuations in fluid mixtures. II. - Mazo, Robert M.; Matteoli, Enrico; Smith, Paul E. (My University, 2009)
The method developed in a previous paper [R. Mazo, J. Chem. Phys. 129, 154101 (2008)] for extracting information on the size of relative fluctuations in multicomponent systems is tested on ten binary systems and one ternary system. For the binary systems, it is found that the approximation works well for mole fractions in the range of 0.15–0.85 in most cases. For the ternary case, the method inherently yields less information and is valid only over a more restricted range for the case studied (chloroform-methanol-acetone). It is found that the predicted ratio of number fluctuations is approximately equal to the ratio of molar volumes of the components.
Keywords: Fluctuations; Liquid mixtures; Liquid theory; Organic compounds; Thermodynamic properties